Candidatura avulsa: análise a partir da democracia constitucional brasileira de 1988 - Fiod, Miguel Dunshee de Abranches (2022)
The high degree of disbelief and dissatisfaction of Brazilian society with the political class, reaching party legends, with a growing distance between representative and represented. Within this context, the proposal for an independent candidacy appears as a possible alternative in this scenario of crisis of representation. Within the scope of the Federal Supreme Court, the issue had a recognized general repercussion, but the matter has not yet been defined. The present dissertation deals with the current political-party context in Brazil and questions the monopoly of political parties in relation to candidacies, to address the problem of compatibility between the single candidacy system and the Federal Constitution. To reach this answer it was necessary to go through the following path. First, it was to understand the role that political parties have within the context of the 1988 Constitution and the way in which they were structured in Brazil. The second was to analyze the paradigm of constitutional democracy as an instrument of political representation and the existing formulas to combat the current crisis of representative democracy. The third was to verify how the single candidacy has been applied in the world, especially in Latin America, as well as the judgments that took place in the Inter-American Court of Human Rights. The study showed that the prohibition of the institute of the single candidacy being (or not) insurmountable for the international law of human rights is fundamental for the solution of the problem. He concluded that it is possible to equate the Pact of San José of Costa Rica with the constitutional norm, as it refers to human political rights, given that the Constitution does not prevent citizens from investing as a candidate. It was also highlighted that the deformities of political representation weaken the very relationship of representation, showing the importance of the constitutional paradigm to preserve the constitutional guarantees in expanding the people's power of choice, to ensure the rights of freedom and guarantee of fulfilling political rights. Political parties would become a way and not the only way for an individual to participate in the electoral process in Brazil